(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the vulnerability of Nghe An health sector to climate change in 2023. Objectives and methods: Using the V&A Assessment Kit to assess the vulnerability and adaptive capacity to climate change in the health sector based on data collected at several research sites from January 2023 to December 2023. Results: The exposure level is at an average level, the exposure score is 2.27, the assessment score of the indicators in the “sensitive” group is 2.08, classified as medium risk. Conclusion: The vulnerability of Nghe An health sector to the impacts of climate change in 2023 is at a medium risk level.